Chromosome alignment and Kif18A action rely on spindle-localized control of Cdk1 activity - Serpico, Angela Flavia; Pisauro, Caterina; Trano, Asia; Grieco, Domenico (Frontiers in Cell and Developmental Biology, 2024)
IntroductionDuring mitosis, chromosome alignment at the mitotic spindle equator grants correct chromosome segregation and proper nuclei formation in daughter cells. The kinesin 8 family member Kif18A plays a crucial role for chromosome alignment by localizing at the kinetochore-microtubule (K-MT) plus ends to dampen MT dynamics and stabilize K-MT attachments. Kif18A action is directly antagonized by the master mitotic kinase cyclin B-dependent kinase 1 (Cdk1) and is promoted by protein phosphatase 1 (PP1). Since chromosome alignment precedes Cdk1 inactivation by cyclin B proteolysis, it is unclear how Kif18A evades Cdk1 inhibition.MethodsWe analyzed chromosome alignment and Kif18A in mitotic cells upon genetic perturbation of the phosphorylation-dependent inhibitory control of Cdk1 activity by immunofluorescence and cell fractionation experiments.ResultsWe show here that chromosome alignment in human cells relies on a recently identified fraction of Cdk1 that is inhibited by Wee1-dependent phosphorylation in mitosis (i-Cdk1, standing for inhibited/inactive-Cdk1) and that localized at spindle structures where it promotes proper spindle assembly. Indeed, the reduction of i-Cdk1 led to several spindle defects including spindles with misaligned, bipolarly attached chromosomes showing poor Kif18A localization at their K-MT plus ends. Restoring i-Cdk1 reversed both alignment defects and Kif18A localization. In cells with lowered i-Cdk1, expressing a phosphonull Kif18A mutant version at the sites that serve as Cdk1 substrate significantly rescued the alignment defects.DiscussionMechanistically, our evidence suggests that i-Cdk1 and active PP1 facilitated the dephosphorylation and reactivation of spindle-localized Kif18A. Considering the relevance of Kif18A for survival of aneuploid cancer cells and the potential therapeutic targeting of both Kif18A and Wee1, these findings could also be relevant for cancer therapy.